Development and validation of a nomogram combining pain score with laboratory indicators for predicting persistent organ failure in acute pancreatitis: a retrospective cohort study - Xing, Jiayu; Xu, Musen; Xu, Jiale; Liu, Jiao; He, Fang (Frontiers in Medicine, 2024)
Background Acute pancreatitis is an inflammatory disease that can lead to persistent organ failure (POF), which is associated with increased morbidity and mortality. Early prediction of POF in AP can significantly improve patient outcomes. Objective To develop and validate a nomogram that combines pain score with laboratory indicators for predicting POF in patients with AP. Methods A retrospective cohort study was conducted, including patients diagnosed with AP. Pain score and laboratory indicators were collected within the first 24 h of admission. A nomogram was developed using logistic regression models and validated in a separate cohort. Results There were 807 patients in the training cohort and 375 patients in the internal validation cohort.Multivariate logistic regression demonstrated that pain score, serum creatinine, hematocrit, serum calcium, and serum albumin were independent risk factors for the incidence of POF in patients with AP. The area under the curve of the nomogram constructed from the above factors were 0.924, respectively. The model demonstrated good calibration and discrimination in both the development and validation cohorts. Conclusion The nomogram had a good performance in predicting POF in patients with AP and can be used to guide clinical decision-making.